Optic nerve sheath meningioma detected by single- photon emission computed tomography/computed tomography somatostatin receptor scintigraphy: a case report. (December 2016) - Nussbaum-Hermassi, Lucie; Ahle, Guido; Zaenker, Chistophe; Duca, Camelia; Namer, Izzie
Abstract Background Optic nerve sheath meningiomas account for only 2 % of orbital lesions and 42 % of optic nerve tumors. Diagnosis remains difficult because histologic confirmation carries a high risk of visual loss. Therefore, a less invasive and specific diagnostic method for differentiating optic nerve sheath meningiomas from other optic nerve lesions is needed to overcome the limitations of computed tomography and magnetic resonance imaging, and make the best individualized treatment decision. This case is a good illustration of the clinical and imaging difficulties inherent in this rare tumor, which may be hard to differentiate from other causes. Case presentation A 51-year-old Caucasian woman developed a central scotoma, visual loss, and abnormal visual evoked potentials. The first magnetic resonance imaging scan classified the optic nerve damage as retrobulbar optic neuritis. After magnetic resonance imaging follow-up at 3 months, a negative lumbar puncture and biological workup, and clinical worsening, an optic nerve sheath meningioma was suspected. We confirmed this diagnosis with111 In-pentetreotide single-photon emission computed tomography, which is able to bind with very high affinity to somatostatin receptor subtype 2 expressed on meningiomas. Conclusions In the diagnosis of optic nerve sheath meningiomas, [111 In]-pentetreotide single-photon emission computed tomography-fused magnetic resonance imaging is a valuable additional tool, optimizing the diagnosis and obviating the need for a more invasive procedure.